PEMANFAATAN MULTIPLICATION BOARD GAME INTERAKTIF UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IV SDN 11 TULANG BAWANG UDIK - Lovandri Dwanda Putra; Anggun Liana Dewi; Alif Fathul Zahra; Maya Tri Aprillia (STKIP Subang, 2024)
Mathematics is an important subject and its applications are widely used in everyday life. However, many students find it difficult to learn mathematics, including elementary school students. This research aims to implement gamification elements in the multiplication board game which is used to help students understand the concept of multiplication in mathematics learning for class IV students at SDN 11 Tulang Bawang Udik. There are many gamification elements such as: points, badges, leaderboards, challenges, competitions, feedback, time pressure and rewards. However, generally the gamification elements that are often used are points, challenges and time pressure. These gamification elements are related to the use of multiplication board games, such as challenges that require students to be able to solve questions correctly, the time given at each level varies, namely 45 and 60 seconds at certain levels, students who can solve questions correctly and on time. will get a reward in the form of points. Gamification increases students' interest in mathematics learning by making the learning experience interactive and fun, as demonstrated by the application of this open media. In conclusion, gamification can help increase student motivation in learning mathematics.